The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1534/genetics.114.168617
|View full text |Cite
|
Sign up to set email alerts
|

Shared Genetic Pathways Contribute to the Tolerance of Endogenous and Low-Dose Exogenous DNA Damage in Yeast

Abstract: DNA damage that escapes repair and blocks replicative DNA polymerases is tolerated by bypass mechanisms that fall into two general categories: error-free template switching and error-prone translesion synthesis. Prior studies of DNA damage responses in Saccharomyces cerevisiae have demonstrated that repair mechanisms are critical for survival when a single, high dose of DNA damage is delivered, while bypass/tolerance mechanisms are more important for survival when the damage level is low and continuous (acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…However, these observations do not indicate that DDT pathways primarily operate in G2 phase in normal cells. Instead, PCNA ubiquitination-mediated HDR appears to operate predominantly in S phase even behind replication forks (Karras and Jentsch 2010;Huang et al 2013;Lehner and Jinks-Robertson 2014). Other studies have demonstrated that RAD5-deficient cells challenged with relatively high doses of DNA-damaging agents progress slowly through S phase or fail to complete S phase with an accumulation of replication intermediates.…”
Section: Cell Cycle-dependent Ddt Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these observations do not indicate that DDT pathways primarily operate in G2 phase in normal cells. Instead, PCNA ubiquitination-mediated HDR appears to operate predominantly in S phase even behind replication forks (Karras and Jentsch 2010;Huang et al 2013;Lehner and Jinks-Robertson 2014). Other studies have demonstrated that RAD5-deficient cells challenged with relatively high doses of DNA-damaging agents progress slowly through S phase or fail to complete S phase with an accumulation of replication intermediates.…”
Section: Cell Cycle-dependent Ddt Regulationmentioning
confidence: 99%
“…In S. cerevisiae, many studies have shown that a deficiency in PCNA ubiquitination-mediated DDT does not impede bulk replication of genomes containing damaged DNA but instead induces a G2 phase cell cycle arrest via checkpoint activation, suggesting that PCNA ubiquitination-mediated DDT is involved in the repair of gaps generated during replication of lesion-containing genomic DNA. This phenotype of DDT-deficient cells appears when cells are challenged with relatively low doses of DNA-damaging agents (Hishida et al 2009;Daigaku et al 2010;Karras and Jentsch 2010;Huang et al 2013;Lehner and Jinks-Robertson 2014). Under such conditions, genetically manipulated yeast strains in which PCNA is ubiquitinated or TLS pols are expressed only in G2, but not in S phase, tolerate damaging agents as well as the wildtype strain, demonstrating that the replication fork structure is not required for the operation of TLS or HDR, and instead that the gaps left behind the replication fork are the substrates for TLS and HDR (Daigaku et al 2010;Karras and Jentsch 2010).…”
Section: Cell Cycle-dependent Ddt Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that TS precedes TLS was proposed based on experiments in which cells exposed to acute methyl methanesulfonate (MMS) treatment (0.033%, 30 min) were released into S phase ( 23 ). However, another study with CLUV showed a synergistic effect in TLS- and TS-deficient mutants, indicating that TLS and TS are interchangeable for survival ( 24 ). Under exposure to low-dose MMS (0.001%), cells have a preference for TS, which operates earlier, whereas TLS is executed later.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that during unperturbed replication and at very low levels of DNA damage, Rad18-dependent DDT is the pathway of choice, with the error-free Rad5-(and Rad51-) dependent template switch operating during S phase, and error-prone synthesis active mainly on ssDNA gaps in G 2 (Hishida et al 2010;Huang et al 2013;Lehner and Jinks-Robertson 2014). We postulate that this error-free pathway is stimulated by Uls1.…”
Section: Discussionmentioning
confidence: 85%